Naming Places Of Worship In Lamongan: Language Identity Linguistic Landscape Studies - Qulub, Muhammad Farihul (PAROLE: Journal of Linguistics and Education, 2024)
This study aims to investigate and reconstruct the language identity in Lamongan as Adipura City. The problem focuses on how the form and pattern of language identity in Lamongan to maintain Adipura City in East Java. This research uses Linguistic Landscape Theory, which describes lingual existence, linguistic ideology, and lingual competition. The research method uses a phenomenological approach with a qualitative descriptive type of research, although some information uses numerical data. The target of the study is language identity in Lamongan with the most popular language pattern instruments, namely Indonesian, Arabic, Javanese, Sanskrit. The research target can formulate a pattern of language identity in Lamongan as a cultural and religious center. The results of the study can model the language identity scheme in Lamongan in the pattern of language choice towards naming places of worship, bilingual Indonesian and Arabic are more dominant, but also found Indonesian, Arabic, Javanese to Sanskrit contained in monolingual and multilingual which there are patterns of language choice found in Lamongan